Numerical Study of Thermal Shock Damage Mechanism of Polycrystalline Ceramics - Gong, Zhenyuan; Guan, Kang; Rao, Pinggen; Zeng, Qingfeng; Liu, Jiantao; Feng, Zhiqiang (Frontiers in Materials, 2021)
A dual-scale model is proposed to study the effect of microstructure parameters (grain size, grain boundary fracture energy) on thermal shock damage mechanism on an example of alumina. At microscale, Representative Volume Element (RVE) models generated by Voronoi tessellation are simulated to obtained mechanical parameters for macro model. At macroscale, a coupled thermomechanical model based on finite-discrete element method (FDEM) is applied to simulate the crack nucleation and propagation. Energy dissipation (ALLDMD) is introduced to investigate the thermal shock cracking mechanism combining crack patterns and crack density, which indicates that decreasing grain size and increasing grain boundary fracture energy have a positive effect on thermal shock resistance. The proposed models not only predict the critical stress temperature which is well consistent to the theoretical thermal shock resistance factor, but also quantify two unconsidered stages previously (crack nucleation and crack instability stage). Our models suggest the crack nucleation and instability will not occur immediately when the model reaches to critical stress, but the models can sustain for higher temperature difference. The thermal shock damage mechanism and the influence of microstructural parameters on thermal shock resistance has also been discussed in detail.